Respuesta :
Answer:
(4;-1).
Step-by-step explanation:
1) to write new equation:
f(x-2)=(x-2)²-4(x-2)+3; ⇒ f(x-2)=x²-8x+15;
2) to define the new vertex:
(4; -1).
PS. the suggested way is not the shortest one; it's just to move the vertex to the right direction on 2 units.
Answer:
Vertex of g(x) is (4, -1)
Step-by-step explanation:
Method 1
Using translations rules:
[tex]\textsf{when }\:a > 0: \quad f(x-a) \implies f(x) \: \textsf{translated}\:a\:\textsf{units right}[/tex]
[tex]\textsf{Therefore }\quad f(x-2) \implies f(x) \: \textsf{translated}\:2\:\textsf{units right}[/tex]
If the vertex of f(x) is (2, -1)
then the vertex of g(x) is (2 + 2, -1) = (4, -1)
Method 2
Vertex form of a parabola
[tex]y=a(x-h)^2+k[/tex]
(where (h, k) is the vertex and a is some constant)
Given function: [tex]f(x)=x^2-4x+3[/tex]
If the vertex of f(x) is (2, -1), then f(x) written in vertex form is:
[tex]f(x)=(x-2)^2-1[/tex]
[tex]\begin{aligned} \textsf{If}\quad g(x) & =f(x-2)\\\implies g(x) &=((x-2)-2)^2-1\\&=(x-4)^2-1\end{aligned}[/tex]
Therefore, the vertex of g(x) is (4, -1)